Adult Children's Educational Attainment and Parent Health in Mid- and Later-Life. (17th June 2021) - Dennison, Christopher R; Lee, Kristen Schultz
Abstract: Objectives: Intergenerational models of adult health contend that children's educational attainments influence the health and well-being of their parents. However, it is unclear how much of this association is confounded by background characteristics that predict both children's educational attainments and parents' subsequent health, particularly in the United States. Methods: Data from the National Longitudinal Study of Adolescent to Adult Health Parent Study are used to examine how having no children who completed college influences parents' self-rated health and depressive symptoms. We rely on propensity score methods to more squarely assess this relationship net of potential confounding bias and to test for heterogeneity in the consequences associated with having no children who completed college. Results: Having no children who completed college is negatively associated with parents' self-rated health and positively associated with depressive symptoms. After statistically balancing differences in background characteristics between groups, these associations remain, though the magnitude of the coefficients is attenuated. Supplemental matching analyses suggest that while the association between children's education and self-rated health might be spurious, the association with depressive symptoms is more robust. Additionally, among parents with the highest propensity for having no children who complete college, the consequences on depressive symptoms are greatest. Discussion: This study pays particular attention to selection-related concerns surrounding the association between offspring educational attainment and parent well-being in the United States. These findings are important given the call for investments in children's educational opportunities as promoting both the well-being of adult children and their parents.